T Helper Cells in the Immunopathogenesis of Systemic Sclerosis – Current Trends - Krasimirova E. (Sciendo, 2017)
Systemic sclerosis (SSc) is a chronic progressive autoimmune disease characterized by skin and multiorgan involvement with alterations in both the innate and adaptive immunities. The hallmark of the disease is widespread fibrosis engaging the skin and multiple internal organs, as well as the musculoskeletal system. There is mounting evidence that T cells are key players in the pathogenesis of scleroderma. The current review discusses the role of the different T helper (Th) lymphocyte subsets in the processes of inflammation and fibrosis, characteristics for the pathogenesis of the disease. Cytokines produced by Th cell populations have a major effect on endothelial cells and fibroblasts in the context of favoring/inhibiting the vasculopathy and the fibrosis spread. The Th2 pro-fibrotic cytokines IL-4 and IL-13 have been shown to induce collagen synthesis by fibroblasts, whereas IFN-γ demonstrates an inhibitory effect. Increased Th17 cells are present in the scleroderma skin infiltrates. The combination of IL-17, IFN-γ and TGF-β levels in CD45RO and CD45RA cells from patients with SSc is useful to distinguish between the limited and the diffuse phenotype of the disease. There are accumulating data for functional and numerical alterations in the Tregs in SSc. High levels of TNF-α which might reduce the suppressive ability of Tregs have been described. According to some studies, the number of Tregs in scleroderma skin biopsies has been decreased against the normal absolute number of Tregs in peripheral blood of the same patients, which suggests suppressed immunomodulatory response. Other studies reported increased frequency of Tregs in peripheral blood of patients with systemic sclerosis and established a correlation with disease activity. The main immunological challenge remains the identification of the trigger of the autoimmune response in SSc, the causes for preferential Th2-type cell responses and the immunological differences between the diffuse and the limited cutaneous form of the disease.